Analisis Struktural pada Naskah Drama “Badai Sepanjang Malam” Karya Max Arifin - Nur Azizah Puspa Tri Utami; Meydita Hidayat; Elysa Febriyanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research examines the drama script "Storm Throughout the Night" by Max Arifin with a structural approach. This drama raises the main theme of the conflict between idealism and reality in everyday life, especially regarding environmental changes from cities to villages. Through analysis of intrinsic elements such as theme, characters, plot, setting, language style, and message, it was found that the main characters, Jamil and Saenah, face inner conflicts between expectations and reality as well as personal values ​​and social pressure. The storyline depicts their emotional and mental journey in adapting to a new environment and searching for identity. This research shows the importance of maintaining loyalty to idealistic values ​​and the importance of dialogue and interaction in facing social challenges. A structural approach helps reveal the relationships between elements in a drama text, providing a deeper understanding of the meaning and message of this literary work.